Super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity and preparation method of super-hydrophobic porous fluorine / aluminum energetic material

By preparing porous fluorine/aluminum energy-containing materials composed of fluorine-containing thermoplastics, aluminum powder, etc., the problem of high energy and time required for laser ignition in the prior art is solved, and the adjustment of laser ignition sensitivity and high-efficiency combustion are achieved.

CN119708728AInactive Publication Date: 2025-03-28HARBIN INST OF TECH +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411809956.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing energy-containing materials require higher energy and time during laser ignition and have low sensitivity, resulting in low combustion efficiency and slow reaction kinetics.

Method used

The superhydrophobic porous fluorine/aluminum energy-containing material consisting of fluorothermoplastics, aluminum powder, metal compounds, solvents, non-solvents and non-spherical conductive nanofillers is used to adjust the composition ratio of the material and the preparation method to achieve adjustability of laser ignition sensitivity.

Benefits of technology

It improves the sensitivity and efficiency of laser ignition, can achieve rapid excitation at lower laser energy, and the material has excellent superhydrophobic properties, which is suitable for use in humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708728A_ABST
    Figure CN119708728A_ABST
Patent Text Reader

Abstract

The invention relates to the field of energetic materials, in particular to a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity and a preparation method. The problems that time and energy consumption needed by laser ignition formed in the common technology are large, and laser sensitivity is low are solved. The super-hydrophobic porous fluorine / aluminum energetic material with the adjustable laser ignition sensitivity is prepared from fluorine-containing thermoplastic plastic, aluminum powder, a metal compound, a solvent, a non-solvent and non-spherical conductive nanofiller. The super-hydrophobic aluminum-based energy-containing composite material has excellent super-hydrophobic performance, it can be ensured that the aluminum-based energy-containing composite material can be stored for a long time in a humid environment without reducing the active content of the aluminum-based energy-containing composite material, the laser ignition sensitivity can be adjusted, and the energy-containing composite material can be rapidly excited under the action of certain laser energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energetic materials, and in particular to a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity and a preparation method thereof. Background Art

[0002] Energetic materials are substances that store a large amount of chemical energy and can be released quickly when needed. These materials have become the first choice for propellants and fuel additives. However, as the particle size of aluminum powder continues to decrease, its reactivity continues to increase. It is very easy to undergo oxidation reaction with oxygen and moisture in the air to form an inactive aluminum oxide layer. The high melting point of the aluminum oxide layer is not conducive to the combustion of aluminum powder.

[0003] The high melting point of alumina (~2100°C) will increase the initial reaction temperature, reduce the combustion speed, and intensify the sintering of the aluminum core during the reaction, resulting in incomplete combustion, low combustion efficiency, slow reaction kinetics, and reduced heat release. At the same time, the action time and energy consumption required for laser ignition increase, which is not conducive to the rapid start-up of the energy of energetic materials.

[0004] On the other hand, traditional energetic composites are usually dense solids with low laser sensitivity, and therefore often require higher laser energy to excite them.

[0005] Therefore, it is urgent to propose a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity and a preparation method to solve the above technical problems. Summary of the invention

[0006] The present invention is to solve the problems of long time and energy consumption and low laser sensitivity of laser ignition formed by conventional technology. A brief overview of the present invention is given below to provide a basic understanding of certain aspects of the present invention. It should be understood that this overview is not an exhaustive overview of the present invention. It is not intended to identify the key or important parts of the present invention, nor is it intended to limit the scope of the present invention.

[0007] The technical solution of the present invention:

[0008] A super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity, the super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity is composed of fluorine-containing thermoplastic plastic, aluminum powder, metal compound, solvent, non-solvent and non-spherical conductive nanofiller;

[0009] The mass fraction of the fluorine-containing thermoplastic plastic is 30-70%, the mass fraction of the aluminum powder is 30-70%, the mass fraction of the metal compound is 0-40%, and the mass fraction of the non-spherical conductive nano filler is 0-10%.

[0010] Preferably, the fluorine-containing thermoplastic is one or more of polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-trifluoroethylene copolymer, and perfluorosulfonic acid resin.

[0011] Preferably, the aluminum powder has a size of 100 nm-10 um and an active aluminum content greater than 70%.

[0012] Preferably, the metal compound is one or more of copper oxide, iron oxide, ferrous oxide, bismuth trioxide, tungsten oxide, cobalt oxide, palladium oxide, vanadium pentoxide, manganese dioxide, chromium trioxide, potassium permanganate, bismuth fluoride, iron fluoride, cobalt fluoride, nickel fluoride, copper fluoride, ferrous fluoride, silicon fluoride, and boron fluoride.

[0013] Preferably, the non-spherical conductive nanofiller is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, single-layer graphene, multi-layer graphene, graphene oxide, and silver nanowires.

[0014] Preferably, the solvent is one or more of acetone, tetrahydrofuran, methyl ethyl acetone, dimethylformamide, dimethylacetamide, tetramethyl urea, dimethyl sulfoxide, trimethyl phosphate, N,N-dimethylformamide, and N-methylpyrrolidone.

[0015] Preferably, the non-solvent is one or more of water, methanol, ethanol, propanol, butanol and carbon tetrachloride.

[0016] A method for preparing a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity comprises the following steps:

[0017] Step 1: Dissolve the fluorine-containing thermoplastic in the solution, and after it is completely dissolved, add aluminum powder and metal compound and stir evenly to form a mixed solution;

[0018] Step 2: Add the mixed solution into the non-solvent in a stirring state, and after the mixture is completely precipitated, pour in the non-spherical conductive nanofiller and stir evenly;

[0019] Step 3: After stirring evenly, filter it and then perform hot pressing to obtain a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity.

[0020] A method for preparing a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity comprises the following steps:

[0021] Step 1: Dissolve the fluorine-containing thermoplastic in the solution, and after it is completely dissolved, add aluminum powder and metal compound and stir evenly to form a mixed solution;

[0022] Step 2: Pour the non-spherical conductive nanofiller and the non-solvent into the mixed solution, and after freeze-drying, obtain the laser ignition sensitivity adjustable, super-hydrophobic porous fluorine / aluminum energetic material

[0023] The present invention has the following beneficial effects:

[0024] The manufacturing process of the present invention is simple and efficient, does not require the use of specific instruments and equipment, can be prepared into various required shapes according to needs, and the safety of the preparation process is effectively guaranteed;

[0025] The present invention has excellent super-hydrophobic properties, and can ensure that the aluminum-based energetic composite material can be stored for a long time in a humid environment without reducing the active content therein;

[0026] The laser ignition sensitivity of the present invention is adjustable, and the energetic composite material can be rapidly excited under the action of a certain laser energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the electron microscope image of the microstructure of the final product and the schematic diagram of the water contact angle;

[0028] Figure 2 It is a schematic diagram of the water contact angle of aluminum powder;

[0029] Figure 3 It is a comparison chart of the energy required for laser ignition of traditional thermite and energetic composite materials prepared in the examples. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described below by the specific embodiments shown in the accompanying drawings. However, it should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0031] Specific implementation method 1: Combination Figure 1-Figure 3 The present embodiment is described. The present embodiment is a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity. The super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity is composed of fluorine-containing thermoplastic plastic, aluminum powder, metal compound, solvent, non-solvent and non-spherical conductive nanofiller;

[0032] The mass fraction of the fluorine-containing thermoplastic plastic is 30-70%, the mass fraction of the aluminum powder is 30-70%, the mass fraction of the metal compound is 0-40%, and the mass fraction of the non-spherical conductive nano filler is 0-10%.

[0033] Specific implementation method 2: Combination Figure 1-Figure 3The present embodiment is described. The present embodiment is a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity. The fluorine-containing thermoplastic plastic is one or more of polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-trifluoroethylene copolymer, and perfluorosulfonic acid resin. These fluorine-containing thermoplastic plastics are particularly suitable for preparing composite materials with special functions due to their excellent chemical stability, heat resistance and mechanical properties.

[0034] Fluorine-containing thermoplastics with a melting point below 200°C and a fluorine content of 40-60% are preferably used to prepare energetic materials, which can not only obtain excellent functional properties, but also simplify the processing flow, improve safety and economic benefits, and meet a wide range of industrial application needs.

[0035] Specific implementation method three: Combination Figure 1-Figure 3 This embodiment is described. This embodiment is a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity. The aluminum powder refers to aluminum powder with high activity, and its particle size range is between 50 nanometers (nm) and 50 micrometers (μm), and the preferred range is between 100 nanometers (nm) and 10 micrometers (μm). Highly active aluminum powder usually has a smaller particle size, a larger specific surface area and stronger chemical reactivity, so it is widely used in the fields of fuel, explosives, alloys, coatings, etc. By adjusting the particle size of the aluminum powder, its reactivity and other physical and chemical properties can be controlled.

[0036] In addition, the aluminum powder can also be compounded by the above two aluminum powders of different sizes, so that the comprehensive performance of the aluminum powder can be better adjusted to meet specific application requirements.

[0037] The aluminum powder described above has an effective active ingredient greater than 60%, and preferably an active aluminum content greater than 70%. This aluminum powder is characterized by higher chemical reactivity, and is usually processed through special processing techniques (such as ball milling, surface treatment, etc.) to improve its activity and enhance the surface energy and reaction rate of the aluminum powder. Highly active aluminum powder is usually used in applications that require rapid response, such as thermal energy release, propellants, rocket fuel, aluminum thermite reaction, etc. In these fields, the higher the active ingredient of the aluminum powder, the faster the reaction rate and the stronger the energy release. The compound may be a mixture of aluminum powders of different specifications and activity levels to further optimize reactivity, stability and other properties to meet specific technical requirements.

[0038] Specific implementation method four: Combination Figure 1-Figure 3This embodiment is described. This embodiment is a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity. The metal compound is one or more of copper oxide, iron oxide, ferrous oxide, bismuth trioxide, tungsten oxide, cobalt oxide, palladium oxide, vanadium pentoxide, manganese dioxide, chromium trioxide, potassium permanganate, bismuth fluoride, ferric fluoride, cobalt fluoride, nickel fluoride, copper fluoride, ferrous fluoride, silicon fluoride, and boron fluoride. The combination of these metal compounds achieves multifunctional performance by adjusting the proportion and type. For example, the combination of bismuth fluoride and iron oxide can improve the ignition performance and heat release characteristics of the material, while different combinations of fluorides and oxides can adjust the ignition sensitivity, reaction time, and energy density. This composite design makes the material adjustable and the performance of the material can be customized according to specific needs.

[0039] In addition, by controlling the size of the metal compounds, especially in the range of 20nm to 50μm, preferably between 20nm-1μm, the performance of these metal compounds in energy materials can be significantly improved. The control of size can not only improve the reaction speed, energy density and stability, but also optimize the dispersion, processability and adaptability of the material in different environments. The performance of the material can also be further adjusted by compounding the above sizes to achieve more refined performance regulation to meet the needs of different application fields.

[0040] Specific implementation method five: Combination Figure 1-Figure 3 This embodiment is described. This embodiment is a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity. The non-spherical conductive nanofiller is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, single-layer graphene, multi-layer graphene, graphene oxide, and silver nanowires. The above fillers are helpful to improve the electrical conductivity and thermal conductivity of the material. When the laser is irradiated to the surface of the material, the nanofiller can quickly absorb and conduct the laser energy, increase the local temperature of the material, and thus promote laser ignition. By accurately controlling the type, shape, and content of these conductive nanofillers, the laser response speed and ignition sensitivity of the material can be finely adjusted.

[0041] Nano-scale fillers have a large specific surface area and can absorb more laser energy under laser irradiation and convert it into heat energy. In addition, the surface of the conductive nanomaterial can form a composite structure with the fluorine / aluminum-based energetic material to improve the surface activity of the material, making it more efficient in absorbing laser radiation. This composite structure is also porous, which can enhance the mechanical strength and thermal fatigue resistance of the material and prevent material failure due to overheating during laser ignition.

[0042] The two-dimensional structures of graphene and graphene oxide in particular can enhance their interaction with light, leading to a stronger thermal response of the material when exposed to high-intensity laser light.

[0043] Specific implementation method six: Combination Figure 1-Figure 3 The present embodiment is described. The present embodiment is a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity. The solvent is one or more of acetone, tetrahydrofuran, methyl ethyl acetone, dimethylformamide, dimethylacetamide, tetramethyl urea, dimethyl sulfoxide, trimethyl phosphate, N,N-dimethylformamide, and N-methylpyrrolidone. By reasonably selecting the solvent, the reactivity of the fluorine / aluminum-based composite material can be precisely controlled, polar molecules can be effectively dissolved, aluminum powder or other energetic substances can be evenly dispersed in the solution, particle agglomeration can be avoided, and the uniformity and controllability of the composite material can be improved, thereby optimizing its laser ignition performance.

[0044] For example, N-methylpyrrolidone and dimethylacetamide can promote the cross-linking and structural adjustment of molecules or polymer chains in the synthesis of energetic materials, improve the mechanical properties and thermal stability of composite materials. They can regulate the formation process of chemical bonds in energetic materials, make the final porous structure more uniform, and thus optimize the reactivity of laser ignition.

[0045] When selecting solvents for laser ignition sensitivity-adjustable, superhydrophobic porous fluorine / aluminum energetic materials, solvents with boiling points below 150°C and low toxicity have significant advantages. These solvents can not only meet the dissolution and dispersion requirements of composite materials, but also ensure safety and environmental friendliness during processing.

[0046] Specific implementation method seven: Combination Figure 1-Figure 3 This embodiment is described. This embodiment is a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity. The non-solvent is one or more of water, methanol, ethanol, propanol, butanol, and carbon tetrachloride. Reasonable selection and proportion are the key to preparing the super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity. By adjusting the use of the non-solvent, the surface properties, porosity, and laser ignition threshold of the material can be accurately controlled, thereby optimizing its performance in practical applications.

[0047] By properly mixing water, ethanol and propanol, the advantages of the three can be combined to further optimize superhydrophobicity, porosity and laser ignition sensitivity. Water can effectively promote the generation of bubbles, ethanol helps to adjust the pore morphology, and propanol can further refine the pore structure and improve the uniformity of the pores. By adjusting the ratio of these three solvents, an ideal balance can be found between laser ignition sensitivity and material porosity. Ethanol and propanol can improve the absorption of laser energy and thermal conductivity, thereby achieving the required ignition sensitivity.

[0048] Specific implementation method eight: Combination Figure 1-Figure 3The present embodiment is described. A method for preparing a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity comprises the following steps:

[0049] Step 1: Dissolve the fluorinated thermoplastic in the solution, ensure that it is completely dissolved, then add aluminum powder and metal compounds, stir them thoroughly to form a homogeneous mixed solution, ensure that the aluminum powder and the fluorinated plastic are well dispersed, and provide a uniform matrix for the subsequent material formation;

[0050] Step 2: Add the mixed solution to the non-solvent in a stirring state to precipitate the mixture. The precipitation process helps to form a porous structure. At the same time, the size and distribution of the pores can be controlled by adjusting the type and concentration of the non-solvent. Then, non-spherical conductive nanofillers are added to further improve the conductivity and structural stability of the material.

[0051] Step 3: After the mixture is stirred evenly, it is filtered to remove excess solvent and impurities, and then it is hot-pressed to obtain the target porous fluorine / aluminum energetic material. The hot-pressing process helps to improve the density of the material and further control its porosity and microstructure, ensuring that the final product has the required laser ignition sensitivity and super-hydrophobic properties.

[0052] Specific implementation method nine: Combination Figure 1-Figure 3 The present embodiment is described. A method for preparing a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity comprises the following steps:

[0053] Step 1: Add fluoroplastics to an appropriate solvent and heat to a certain temperature to promote their complete dissolution. After the fluoroplastics are completely dissolved, add aluminum powder and metal compounds. Aluminum powder serves as a heat energy release source in this formula, and metal compounds help optimize reactivity or enhance the stability of the material. These ingredients need to be stirred evenly to ensure that the aluminum powder and metal compounds are evenly distributed in the fluoroplastic matrix. This process has an important impact on the thermal reactivity and laser ignition sensitivity of the material.

[0054] Step 2: Add non-spherical conductive nanofillers to the mixed solution to improve the conductivity of the material and promote heat conduction during laser ignition. Add non-solvents to the mixed solution to cause the components in the solution to condense or precipitate, forming a preliminary solid network with a porous structure. Freeze-dry the mixture with the non-solvent added to obtain the target porous fluorine / aluminum energetic material. This process helps to remove residual solvents and moisture and form a stable porous structure in the material. The freeze-drying process can also accurately control the morphology and distribution of the pores, and the freeze-dried material will have a high porosity and can achieve super-hydrophobicity due to the particularity of its structure. The selection of freeze-drying speed and temperature can further adjust the porosity of the material and its laser ignition response characteristics.

[0055] In addition to the dissolution-phase change-hot pressing method and the dissolution-freeze drying method, the traditional mixing method can also be used, specifically, melting the fluorine-containing thermoplastic plastic at a certain temperature and under stirring, and after the fluorine-containing thermoplastic plastic is completely melted, adding a certain amount of aluminum powder, metal compounds and non-spherical conductive nanofillers to obtain the final product.

[0056] Example 1

[0057] Step 1: dissolving 50 parts of polyvinylidene fluoride in dimethyl sulfoxide solvent under mechanical stirring to prepare a solution with a polymer concentration of 20%;

[0058] Step 2: After the polyvinylidene fluoride is completely dissolved in dimethyl sulfoxide, 50 parts of aluminum powder with a particle size of 5 μm and an effective active ingredient content of 87% are added thereto, and stirring is continued for 30 minutes to obtain a uniformly dispersed mixture;

[0059] Step 3: After stopping stirring, let it stand until the internal bubbles are completely eliminated, and slowly add water. At this time, due to solvent exchange, the polyvinylidene fluoride undergoes a phase transition. Repeat the water washing five times, and then place the obtained product in propanol and soak it for 12 hours. Finally, place it in a freeze dryer for freeze-drying to obtain the final product.

[0060] Example 2

[0061] Step 1: dissolving 60 parts of tetrafluoroethylene-hexafluoropropylene copolymer in N-methylpyrrolidone to prepare a polymer solution with a concentration of 15%;

[0062] Step 2: After the polymer is completely dissolved, add 35 parts of 1um aluminum powder with an active aluminum content of 86%, stir mechanically to mix evenly, and then slowly pour the resulting mixture into a solvent of 1:1 ethanol and water that is vigorously stirred (2000 rpm);

[0063] Step 3: After stirring for 30 minutes, reduce the rotation speed to 60 revolutions per minute, add 5 parts of carbon nanotubes, continue stirring for 1 hour, and then filter and dry to obtain the final product.

[0064] Example 3

[0065] Step 1: dissolving 40 parts of vinylidene fluoride-trifluoroethylene copolymer in N,N-dimethylformamide solvent under mechanical stirring to prepare a polymer solution with a concentration of 20%;

[0066] Step 2: Add 30 parts of aluminum powder with a particle size of 200 nanometers and an activity of 89% and 30 parts of ferric trifluoride under mechanical stirring, and stir mechanically for 1 hour until the mixture is mixed evenly;

[0067] Step 3: Slowly pour the mixture into a solvent containing a large amount of water and ethanol in a ratio of 3:1, finally take out the precipitate, and dry it at 60°C and 1MPa pressure to obtain the final product.

[0068] Example 4

[0069] Step 1: dissolving 60 parts of vinylidene fluoride-trifluoroethylene copolymer in dimethylformamide under mechanical stirring to prepare a 10% polymer solution;

[0070] Step 2: Add 39 parts of aluminum powder with a particle size of 100 nanometers and an activity of 90% and stir for 1 hour to ensure uniform mixing;

[0071] Step 3: Slowly pour the mixture into a solvent of ethanol and water in a ratio of 2:1 under slow mechanical stirring (100 rpm), continue stirring for 20 minutes after the mixture is completely precipitated, then add 1 part of silver nanowires, keep stirring for 30 minutes and filter, then dry at 60°C and 5Mpa pressure to obtain the final product.

[0072] It should be noted that in the above embodiments, as long as the technical solutions are not contradictory, they can be arranged and combined, and those skilled in the art can exhaust all possibilities based on the mathematical knowledge of arrangement and combination. Therefore, the present invention will no longer describe the technical solutions after arrangement and combination one by one, but it should be understood that the technical solutions after arrangement and combination have been disclosed by the present invention.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity, characterized in that: The laser ignition sensitivity adjustable, super-hydrophobic porous fluorine / aluminum energetic material is composed of fluorine-containing thermoplastics, aluminum powder, metal compounds, solvents, non-solvents and non-spherical conductive nanofillers; The mass fraction of the fluorine-containing thermoplastic plastic is 30-70%, the mass fraction of the aluminum powder is 30-70%, the mass fraction of the metal compound is 0-40%, and the mass fraction of the non-spherical conductive nano filler is 0-10%.

2. The laser ignition sensitivity adjustable, super-hydrophobic porous fluorine / aluminum energetic material according to claim 1, characterized in that: The fluorine-containing thermoplastic plastic is one or more of polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-trifluoroethylene copolymer, and perfluorosulfonic acid resin.

3. The laser ignition sensitivity adjustable, super-hydrophobic porous fluorine / aluminum energetic material according to claim 1, characterized in that: The aluminum powder has a size of 100nm-10um and an active aluminum content greater than 70%.

4. The laser ignition sensitivity adjustable, super-hydrophobic porous fluorine / aluminum energetic material according to claim 1, characterized in that: The metal compound is one or more of copper oxide, iron oxide, ferrous oxide, bismuth trioxide, tungsten oxide, cobalt oxide, palladium oxide, vanadium pentoxide, manganese dioxide, chromium trioxide, potassium permanganate, bismuth fluoride, iron fluoride, cobalt fluoride, nickel fluoride, copper fluoride, ferrous fluoride, silicon fluoride, and boron fluoride.

5. The laser ignition sensitivity adjustable, super-hydrophobic porous fluorine / aluminum energetic material according to claim 1, characterized in that: The non-spherical conductive nanofiller is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, single-layer graphene, multi-layer graphene, graphene oxide, and silver nanowires.

6. The laser ignition sensitivity adjustable, super-hydrophobic porous fluorine / aluminum energetic material according to claim 1, characterized in that: The solvent is one or more of acetone, tetrahydrofuran, methyl ethyl acetone, dimethylformamide, dimethylacetamide, tetramethyl urea, dimethyl sulfoxide, trimethyl phosphate, N,N-dimethylformamide, and N-methylpyrrolidone.

7. The laser ignition sensitivity adjustable, super-hydrophobic porous fluorine / aluminum energetic material according to claim 1, characterized in that: The non-solvent is one or more of water, methanol, ethanol, propanol, butanol and carbon tetrachloride.

8. A method for preparing a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity, characterized in that: The steps include: Step 1: Dissolve the fluorine-containing thermoplastic in the solution, and after it is completely dissolved, add aluminum powder and metal compound and stir evenly to form a mixed solution; Step 2: Add the mixed solution into the non-solvent in a stirring state, and after the mixture is completely precipitated, pour in the non-spherical conductive nanofiller and stir evenly; Step 3: After stirring evenly, filter it and then perform hot pressing to obtain a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity.

9. A method for preparing a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity, characterized in that: The steps include: Step 1: Dissolve the fluorine-containing thermoplastic in the solution, and after it is completely dissolved, add aluminum powder and metal compound and stir evenly to form a mixed solution; Step 2: pouring non-spherical conductive nanofillers and non-solvents into the mixed solution, and freeze-drying to obtain a super-hydrophobic porous fluorine / aluminum energetic material with adjustable laser ignition sensitivity.

Citation Information

Patent Citations

  • Meter-level very-high-burning-rate high-energy dense composite material and preparation method thereof

    CN106518583A

  • Aluminum powder surface self-activation method

    CN109293463A

  • Preparation method of polyvinylidene fluoride coated micro / nano aluminum powder

    CN110508802A

  • Combustion explosion multi-mechanism coupling type energetic electromagnetic damage cloud cluster as well as preparation method and application thereof

    CN114478148A

  • Gas-phase fluorinated modified aluminum powder and preparation method thereof

    CN115403431A